Critical Analysis of Administrative Management in the Costa Rican Public Sector - Tullocks Abarca, Julio Antonio (2024)
The management of the Costa Rican public sector has been undergoing a series of changes ranging from administrative management to the focus on the services provided to the user, in addition to the economic crisis that the State is going through, which has contributed to the valuation of the efficiency of its institutions. This has generated challenges that hinder its efficiency, from basic elements of agility and modernization to the provision of services for taxpayers and other users; the lack of transparency in the processes, the quality of services and the non-completion of works have been continuously more noticeable problems, which lead us to ask ourselves which elements affect administrative management.